Pengaruh Pendidikan Kewirausahaan dan Motivasi Usaha terhadap Minat Berwirausaha (Studi pada Mahasiswa Fakultas Ekonomi Universitas Muhammadiyah Ponorogo) - Wira Bharata (CAPITAL: Jurnal Ekonomi dan Manajemen, 2019)
The development of curricula and courses for entrepreneurship education has occurred since the early 80s. Academic institutions have worked hard in developing appropriate entrepreneurship education programs and small businesses. Although its history is relatively short, entrepreneurship education has become a teaching area that is widely recognized and recognized at universities and business schools. However, questions about the effectiveness of entrepreneurship education programs and how strategies are designed to maximize their effectiveness remain unanswered. The content and context of entrepreneurship education programs in various institutions, regions and countries can be different. This research was conducted at the Muhammadiyah Ponorogo University with the student population of Muhammadiyah Ponorogo University. The sampling technique used a systematic random sampling method, with a sample of 50 people. The data obtained was analyzed using the GSCA analysis tool. The results showed that Entrepreneurship Education and Business Motivation would provide a large stimulus to students in relation to Entrepreneurship Intention.Keyword : Entrepreneurship Education, Business Motivation, Entrepreneurship Intention